2012
DOI: 10.1111/j.1538-7836.2012.04914.x
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning reduces thrombus formation in the rat

Abstract: 13 Huang Q, Neuenschwander PF, Rezaie AR, Morrissey JH. Substrate recognition by tissue factor-factor VIIa. Evidence for interaction of residues Lys165 and Lys166 of tissue factor with the 4-carboxyglutamate-rich domain of factor X. J Biol Chem 1996; 271: 21752-7.14 Boettcher JM, Davis-Harrison RL, Clay MC, Nieuwkoop AJ, Ohkubo YZ, Tajkhorshid E, Morrissey JH, Rienstra CM. Atomic view of calcium-induced clustering of phosphatidylserine in mixed lipid bilayers. Biochemistry 2011; 50: 2264-73.Remote ischemic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…For example, an examination of thrombus formation in large arteries (coronary and femoral) subjected to either local or remote (distant tissue) IPC have revealed improved vessel patency, the generation of small thrombi and fewer emboli after a subsequent insult (Hata et al 1998, Ropcke et al 2012). The anti-thrombogenic response of larger arteries to IPC is supported by a report describing attenuation of different molecular indices of platelet activation, including fibrinogen binding and aggregation with neutrophils (Linden et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an examination of thrombus formation in large arteries (coronary and femoral) subjected to either local or remote (distant tissue) IPC have revealed improved vessel patency, the generation of small thrombi and fewer emboli after a subsequent insult (Hata et al 1998, Ropcke et al 2012). The anti-thrombogenic response of larger arteries to IPC is supported by a report describing attenuation of different molecular indices of platelet activation, including fibrinogen binding and aggregation with neutrophils (Linden et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive RIC therapy method was performed as published elsewhere [ 18 , 19 ] with a programmable cuff or its sham procedure with a cuff that did not inflate or deflate ( see detail in “ Supplemental Methods ” ) [ 15 ]. Bilateral RIC therapy was performed in both hind limbs simultaneously (4 cycles × 5 min duration of each cycle inflate and deflate × 5 min interval between each cycle) daily for 1 month (BCAS+RIC-1MO) or 4 months (BCAS+RIC-4MO) after 1 week from BCAS surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Moncada found that preconditioning increases expression of cyclooxygenase 1 and prostacyclin synthase; these enzymes act successively to produce prostacyclin, which inhibits platelet aggregation and vasoconstriction ( 50 ). Røpcke et al also demonstrated that RIPreC reduces arterial thrombus formation and embolization in rats ( 51 ). Several clinical trials are underway to test the safety and efficacy of RIPreC for protecting the brain against anticipated damage ( 52 , 53 ), and its procedural simplicity makes it an excellent candidate for study in future clinical trials.…”
Section: Ric Mechanismsmentioning
confidence: 98%
“…The humoral pathway has been most extensively studied. Some studies have identified specific factors, such as stromal cell-derived factor-1 α, interleukin, nitrite, cysteine-rich secretory protein 3, and microRNA-144 as possible candidate transfer factors ( 51 , 79 , 80 ). Ueno et al suggest that RIPreC transiently increases plasma VEGF levels by downregulating miR-762 and miR-3072-5p in CD34-positive bone marrow cells, leading to protection against organ ischemia ( 81 ).…”
Section: Transfer Of the Cerebral Protective Stimulusmentioning
confidence: 99%